Wastewater treatment using cellulose nanofiber (CNF)-based green filters: A sustainable approach to water purification - M.M. Alam; Md. Johurul Islam; Sumsun Naher; Kenneth T V Grattan; S. Narjim; Claire Heffernan (Carbohydrate Polymer Technologies and Applications)
Nanocellulose (NC), as a material, is attracting considerable attention due to its renewable nature, anisotropic shape, excellent mechanical properties, good biocompatibility, tailorable surface chemistry and interesting optical properties. In addition is it easy to source in many developing countries and is inexpensive, as it is often simply considered as a waste product from banana production. In this study, banana fibers (BFs) are chemically modified and converted into Cellulose NanoFibers (CNFs), for incorporation into water filters. The properties of the CNFs thus created were then characterized by using several analytical techniques, such as scanning electron microscopy (SEM), Fourier Transform Infra-Red (FTIR) spectroscopy, X-ray diffraction (XRD) and a thermal study, to understand them better and thus optimize their properties. The aim in so doing is for the CNFs to be used as the basis for fabricating an innovative and inexpensive design of filter, for water purification, and which can be used locally. The key purpose of the work has been the development of a CNF-based water filter, which was fabricated by using a mixture of locally-sourced kaolin (Bijoypur clay) and CNFs, in a 10:1 wt ratio. The water filters thus fabricated were tested and their performance evaluated by exposure to simulated wastewater, containing a combination of six readily available antibiotics (Ciprofloxacin, Clarithromycin, Erythromycin, Metronidazole, Sulfamethoxazole and Trimethoprim). This evaluation was enabled by using UV–Visible spectroscopy measurements, before and after filtration. These simple, CNF-based water filters were found to be highly effective in removing the antibiotic solution used on each pass through the filter, showing a figure of merit of 2.7 ± 0.1 per pass. This approach to filter production provides a simple, inexpensive environmentally friendly and locally-sourced solution to the reduction of antibiotics in wastewater, reducing the pollution problems those antibiotics entering the wastewater supply causes.